An Analysis of Errors Caused by Omani ESL Learners in Pronouncing Certain Consonant Sounds - Mohammed Alyaqoobi, Zainab; Fatimah, Ali (Global Research & Development Services, 2016)
As the English Language has become the first international and most widespread means of communication in the world, Omani schools and colleges students are obligated to acquire a considerably good level of English. It essential that students who seek the best job opportunities in professional occupations must be equipped with English Language skills. Omani students who are learning English as a foreign language face various problems in learning or acquiring different skills; reading, writing, pronunciation, grammar, and vocabulary. Most of the time, the other components are greatly emphasized in teaching and learning, while pronunciation is hardly touched upon. Consequently, the learners come up with faulty pronunciation which creates big obstacles in the process of communication. Omani ESL learners have problems with the differentiation between the sounds /p/ and /b/, as Arabic does not have the sound /p/. So instead of a ‘big bowl of noodles’ some Omani students pronounce ‘pig pole of noodles’. In addition to that, Omani ESL learners may also fail to differentiate between the /ʧ/ and /ʃ/ sounds. For example, the sound /ʧ/ as in ‘cheap’ /ʧi:p/ is replaced by the sound /ʃ/ as in ‘sheep’ /ʃi:p/. As a result, the problems that face Omani ESL learners are a result of lack pronunciation teaching methods and lack of using modern educational media such as digital language laboratories and audiovisual materials. In additional to that, translate method plays an important role in mispronunciation of /p/ and /ʧ/ sounds by Omani ESL learners in Omani learning institutions.